**Question**

**If A + B = 2C and C + D = 2A, then**

A. A + D = B + C

B. A + C = 2B

C. A + C = B + D

D. A + C = 2D

**Answer: **C

**Solution:**

Given,

A + B = 2C —-(i)

C + D = 2A—-(ii)

Adding (i) and (ii) we get :

=> A + B + C + D = 2C + 2A

=> B + D = A + C

**Question**

**If A + B = 2C and C + D = 2A, then**

A. A + D = B + C

B. A + C = 2B

C. A + C = B + D

D. A + C = 2D

**Answer: **C

**Solution:**

Given,

A + B = 2C —-(i)

C + D = 2A—-(ii)

Adding (i) and (ii) we get :

=> A + B + C + D = 2C + 2A

=> B + D = A + C